Proceso de atención de enfermería en paciente con hidrocefalia. - Lema Ojeda, Luis Ulfredo (2022)
Hydrocephalus is a pathology that consists of the accumulation of cerebrospinal fluid in the skull, which one of its most predominant symptoms is the increase in head circumference in relation to age and temperature rises, in addition to presenting various complications, one of its main treatments is the surgery. Through the nursing care process with the help of functional patterns and an adequate cephalo-caudal assessment, we can establish the necessary nursing care that provides a solution to the affected functional patterns in relation to human responses.